Resilience and its Associated Factors in Clinical Nurses: A Cross-sectional Study - Ghasempour , Saeed; Hosseinzadeh, Ali; Dadgari , Ali; Ebrahimi , Hossein (Shahroud Journal of Medical Sciences, 2023)
Background: Resilience is the positive adaptation of people in reaction to unfavorable conditions. Meanwhile, nursing is a demanding occupation with extensive stress and challenges. Thus, this study was performed to determine the extent of resilience among nurses and its associated factors. Methods: This cross-sectional study was performed on 320 nurses in Shahroud, Iran. Those with bachelor's degree of nursing and above as well as at least one year of full-time clinical practice were chosen through convenience sampling technique. The data collection instruments were included Sherer's General Self-Efficacy Scale and Connor-Davidson Resilience Scale. The data were analyzed by descriptive and inferential statistics (T-test, ANOVA, Pearson correlation coefficient, and multiple linear regression). Results: The present study showed that nurses experienced low levels of resilience (63.31±15.82) and high levels of self-efficacy (62.86±9.62). Furthermore, a positive and significant correlation was observed between resilience and self-efficacy of nurses (r=0.55, P<0.001). Satisfaction with personal protective equipment at the hospital of service and sense of safety against COVID-19 were noted as the factors associated with resilience and self-efficacy of nurses (P<0.05). Conclusion: Based on the results of this study, provision of a safe environment with sufficient personal protective equipment as well as training the resilience skills and enhancing psychological capacity of nurses would play a key role in their positive adaptation to the tough and challenging conditions of the workplace.